Oligocene‐Miocene Great Lakes in the India‐Asia Collision Zone. (26th September 2016) - DeCelles, Peter G.; Castañeda, Isla S.; Carrapa, Barbara; Liu, Juan; Quade, Jay; Leary, Ryan; Zhang, Liyun
Abstract: The Himalayan‐Tibetan Plateau is Earth's highest topographic feature, and formed largely during Cenozoic time as India collided with and subducted beneath southern Asia. The >1300 km long, late Oligocene‐early Miocene Kailas basin formed within the collisional suture zone more than 35 Ma after the onset of collision, and provides a detailed picture of surface environments, processes and possible geodynamic mechanisms operating within the suture zone during the ongoing convergence of India and Asia. We present new geochronological, sedimentological, organic geochemical and palaeontological data from a previously undocumented 400 km long portion of the Kailas basin. The new data demonstrate that this part of the basin was partly occupied by large, deep, probably meromictic lakes surrounded by coal‐forming swamps. Lacustrine facies include coarse‐ and fine‐grained turbidites, profundal black shales and marginal Gilbert‐type deltas. Organic geochemical temperature proxies suggest that palaeolake water was warmer than 25 °C, and cyprinid fish fossils indicate an ecology capable of supporting large fish. Our findings demonstrate a brief period of low elevation in the suture zone during Oligocene‐Miocene time (26–21 Ma) and call for a geodynamic mechanism capable of producing a long (>1000 km) and narrow basin along the southern edge of the upper, Asian plate, long after the onset of intercontinental collision. Kailas basin deposits presently are exposed at elevations >6000 m, requiring dramatic elevation gain in the region after Kailas deposition, without strongly shortening the upper crust. Episodic Indian slab rollback, followed by break‐off and subsequent renewal of flat‐slab subduction, can account for features of the Kailas basin.